Development of a novel multi-epitope subunit mRNA vaccine candidate to combat Acinetobacter baumannii - Shiyang Ma; Fei Zhu; Peipei Zhang; Yizhong Xu; Ziyou Zhou; Hang Yang; Caixia Tan; Jie Chen; Pinhua Pan (Scientific Reports)
Abstract Acinetobacter baumannii, an opportunistic bacterium prevalent in various environment, is a significant cause of nosocomial infections in ICUs. As the causative agent of pneumonia, septicemia, and meningitis, A. baumannii typically exhibits multidrug resistance and is associated with poor prognosis, thus led to a challenge for researchers in developing new treatment and prevention methods. This study involved the development of a novel multi-epitope mRNA vaccine for A. baumannii and validation of in silico approaches was conducted. We screened 11 immunodominant epitopes for cytotoxic T cells, 5 for helper T cells, and 10 for Linear B-cell based on promising candidate proteins omp33-36, ompA and ompW, the selection of these three proteins is based on reverse vaccinology screening and previous work by other researchers. All predicted epitopes demonstrated strong antigenicity, immunogenicity without posing any potential harm to humans. Additionally, high conservancy is required to cover different strains. All epitopes, as well as adjuvants, were constructed into a final vaccine, which was further assessed by calculating its physicochemical properties. Next, we docked the vaccine protein with immune receptors and analyzed the complexes with dynamic simulations to evaluate its affinity to receptors. At last, the constructed sequence is translated to an mRNA sequence. The results indicated the constructed vaccine is capability of eliciting robust humoral and cellular immune responses, making it a promising candidate for protection against the targeted pathogen.